Analisis Pengaruh Financial Development Terhadap Pertumbuhan Ekonomi di Indonesia - Nia Putri Kunanti; Melti Roza Adry (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to determine how the influence of financial development on economic growth in Indonesia. Financial development indicators are M2 money supply, bank assets, private credit and trade openness. Where inflation and trade openness as a control variable and economic growth as the dependent variable. The data used in this study are secondary data from 2005 quarter 1 to 2018 quarter 4 which were collected through documentation and related agencies. This study uses multiple linear regression analysis and error correction models. The results of this study indicate that: (1) the money supply M2 has a negative effect on economic growth in Indonesia; (2) Bank assets have a negative effect on economic growth in Indonesia; (3) Private credit has a positive effect on economic growth in Indonesia; (4)) trade openness has a positive effect on economic growth in Indonesia.